Passion over pragmatism: the motivation of Australian winery owners. (2016) - Charters, Steve; Walker, Beth; Brown, Alan
The Australian wine industry is dominated by small and medium enterprises. Many of these businesses incorporate primary, secondary and tertiary activities which require a range of management skills to succeed in an increasingly competitive market. The motives of owner/managers for being in this industry are varied and potentially impact on the success enjoyed by their business. Using interviews with the owner/managers of small businesses this paper explores these varying motives, how they may change, and their impact on strategies and business performance. Findings suggest two possible dimensions of motivation: firstly a dimension ranging on an axis from passion for making wine to being solely interested in a 'business for profit' and secondly a dimension around being in business for personal or external reasons. Clusters of wineries are identified based on these dimensions, highlighting the diversity of small business owner/managers motivations in this industry. Further, the reasons for entering and staying in the wine industry may change over time.